Peran Pemerintah Dalam Menyelamatkan Naskah Kuno Minangkabau Pasca Gempa Pada Untuk Pelestarian Budaya Masyarakat Minangkabau - Syarif, Viola Dewi Putri (Pustakaloka, 2015)
The manuscripts of Minangkabau has many content about society, lives, and rules, such as the story of the batle that happened at that time, infuential scholars, the natural disasters that have occurred,and traditional medicine,Â  allÂ  ofÂ  itÂ  be writen withÂ  beautifulÂ  handwriting letered Arabic and Malay. On September 30, 2009 an earthquake with a strength of 7.9 on the Richter scale destroyed half of West Sumatera regions, include the buildings of information centers,and the storage areas of ancient texts Minangkabau. That makes all of ancients texts lost and broken. These manuscripts are original publications and unparalleled. This research is to know how the governmentâs role in saving the post-earthquakeÂ  ancientÂ  manuscripts,Â  forÂ  culturalÂ  preservationÂ  societyÂ  of Minangkabau. This study is qualitative, using interview, observationand documentation.Â  ThisÂ  studyÂ  showsÂ  thatÂ  inÂ  theÂ  preservationÂ  ofÂ  the collection of ancient manuscripts damaged afterÂ  theÂ  earthquake, West Sumatera provincial government assisted by the National Library team inÂ  repairingÂ  damaged manuscriptsÂ  collection. NationalÂ  libraryÂ  team brings 17 boxes of ancient manuscripts Minangkabau to be treated. And to replace the lost collection, the government is conductingÂ  a search of the ancient manuscripts in houses to the public because there are still many collection of ancient manuscripts held by the public.